Educational Empowerment of Gypsy Communities in Chakwal: The Jhuggi School Project Initiative - Farida Yunas, (IJLTP, 2025)
This paper explores the Trust for Awareness, Information and Knowledge (TAIK) Welfare Society's Jhuggi School Project in Chakwal, Pakistan, aimed at improving the socio-economic status of the gypsy community through education, health initiatives, and vocational training. The project, established in 2014, focuses on addressing issues like lack of education, poverty, and inadequate health and hygiene practices in the gypsy communities (population 780, sample 189). Key outcomes include increased school enrolments, improved health conditions, and community engagement in alternative livelihoods, marking a significant shift from traditional begging practices.